Porous Hydrophobic–Hydrophilic Composite Hollow Fiber and Flat Membranes Prepared by Plasma Polymerization for Direct Contact Membrane Distillation - Ashok K. Sharma; Adam Juelfs; Connor Colling; Saket Sharma; Stephen P. Conover; Aishwarya A. Puranik; John Chau; Lydia Rodrigues; Kamalesh K. Sirkar (Membranes, 2021)
High water vapor flux at low brine temperatures without surface fouling is needed in membrane distillation-based desalination. Brine crossflow over surface-modified hydrophobic hollow fiber membranes (HFMs) yielded fouling-free operation with supersaturated solutions of scaling salts and their precipitates. Surface modification involved an ultrathin porous polyfluorosiloxane or polysiloxane coating deposited on the outside of porous polypropylene (PP) HFMs by plasma polymerization. The outside of hydrophilic MicroPES HFMs of polyethersulfone was also coated by an ultrathin coating of porous plasma-polymerized polyfluorosiloxane or polysiloxane rendering the surface hydrophobic. Direct contact membrane distillation-based desalination performances of these HFMs were determined and compared with porous PP-based HFMs. Salt concentrations of 1, 10, and 20 wt% were used. Leak rates were determined at low pressures. Surface and cross-sections of two kinds of coated HFMs were investigated by scanning electron microscopy. The HFMs based on water-wetted MicroPES substrate offered a very thin gas gap in the hydrophobic surface coating yielding a high flux of 26.4–27.6 kg/m2-h with 1 wt% feed brine at 70 °C. The fluxes of HFMs on porous PP substrates having a long vapor diffusion path were significantly lower. Coated HFM performances have been compared with flat hydrophilic membranes of polyvinylidene fluoride having a similar plasma-polymerized hydrophobic polyfluorosiloxane coating.